Once more unto the breach, dear friends : incomplete theory and complete bibliography of Irving Louis Horowitz on the occasion of his 75th birthday /: incomplete theory and complete bibliography of Irving Louis Horowitz on the occasion of his 75th birthday. (2017) - Unknown
No abstract available